Uma abordagem das relações métricas no triângulo retângulo para alunos do campo - PONTES, Agnaldo Reis (2020)
This present paper presents a research developed in the Program of Professional Masters in Rural Development and Management of Agri - food Developments of the Federal Institute of Education, Science and Technology of Pará, class of Paragominas. This paper aims to discuss and suggest new approaches that enable improvements in the teaching of mathematics through the insertion of Information and Communication Technologies from the preparation of a didactic sequence for teaching and learning of metric relations in the right triangle using GeoGebra. From the data collected through questionnaires, it was possible to understand the perception of teachers and students regarding the uses of Information and Communication Technologies - ICTs in teaching and learning of mathematics. Mathematics teachers recognize the importance of technological resources for the teaching of mathematics, however, it is observed that the teaching of mathematics, practiced by them, continues to replicate the traditional method of teaching this discipline. With the information collected, after the validation of the didactic sequence, the benefits that ICT can bring to teaching and learning in mathematics are evident